Inhabiting childern : childeren labour and cchooling in postcolonial India - Balagopalan, Sarada (London, 2014)
Although 'multiple childhoods' recognizes children's lives as heterogeneous and culturally inscribed, the figure of the 'victimized' child continues to test the limits of this framework. Inhabiting 'Childhood' ambitiously redresses these limits by drawing on the everyday experiences of street children and child labourers in Calcutta to introduce the postcolony as a critical, and thus far absent, lens in theorizing the 'child'. Through capturing a moment in which global, national and local efforts combined to improve and transform these children's lives through school enrolment and new discourses of 'children's rights', this ethnography makes a vital point about the complexity and contemporaneity of their extensive practices of dwelling generated by the exigencies of survival within postcolonial 'development'. These modes of living labour are central to comprehending why these children, though desirous of the transition from labour to school, find this difficult to inhabit. This book argues that this difficulty, which can be neither dissolved through a 'cultural' understanding of these lives nor resolved within a more technocratic policy norm, is in fact a very productive opening to rethinking 'childhood'.
Keywords: Childlabor